Improving Students' Understanding of Prayer Material in PAI Subjects Through Demonstration Method of Class VII Students of SMP Negeri 2 Minas - Dewi, Sinta; Hertati, Hertati; Rainelda, Rainelda (Indonesian Journal of Basic Education, 2024)
This study aims to improve students' understanding of prayer material in Islamic Religious Education (PAI) subjects through the demonstration method in class VII SMP Negeri 2 Minas. The research method used was Classroom Action Research (PTK) with 39 students as research subjects in 2022. Data were collected through observations, interviews, and student comprehension tests. The results showed that the application of the demonstration method significantly improved students' understanding of the correct prayer procedures. This improvement can be seen from the evaluation results before and after the application of the demonstration method. Thus, the demonstration method can be used as one of the effective learning strategies in improving students' understanding of prayer material.